THE MAPPING OF RARE PLANT SPECIES DISTRIBUTION IN MONKEY FOREST, UBUD, GIANYAR, BALI - Wijana, I Nyoman; Wesnawa, Gede Astra (Universitas Pendidikan Ganesha, 2018)
The purpose of this research was to know the species of rare plants existing in forest tourism Monkey Forest, Ubud, Gianyar, Bali and their mapping distributions in the original nature. This is an explorative research. The populations of this research were all species of plants in Monkey Forest. This research samples were the plant species covered by the squares. The sampling method used was quadratic method with systematic sampling technique. The mapping of rare plant species distribution used simple mapping method which was simple polygon compass and GPS. Identification of rare plant species was conducted through interviews, questionnaires, observations, and document studies. The results showed that the distribution of rare plant species in Monkey Forest, Ubud, Gianyar, Bali was in groups. The total number of rare plant species their nature were 33 species with the details that there were as many as six species of plants belonging to the National Rare category, 18 species of Bali Rare category, eight species of Regency Rare category, and one species of Rare Sub-District category.